Diseño de cimentación superficial aplicando hormigón con fibra de acero para la estabilidad estructural de viviendas - Zamora Villaruel, Jean Carlos (2024)
The present investigation involved the design of a shallow foundation for a threestory house constructed with A-36 steel structure, including the implementation of a grade beam, using specialized software for detailed analysis of both the structure and the foundation. The study area was developed at Km. 12 of the Durán Boliche road. Due to the geographic location of the study area and the type of soil, it was decided to evaluate the mechanical properties of structural concrete by adding 0.25% steel fibers, with curing periods of 7 and 28 days, improving its resistance to microcracking.......